2022
DOI: 10.1002/pc.26809
|View full text |Cite
|
Sign up to set email alerts
|

Current trends, applications, and challenges of coatings on additive manufacturing based biopolymers: A state of art review

Abstract: Healing of bone fractures highly depends on the biocompatibility, stability in biological conditions, biodegradability, technical functionality, and shelf‐life of biomaterials. Metallic biomaterials offer excellent mechanical properties and biocompatibility. However, metallic bone implants result in stress shielding, release of toxic ions, excessive wear, and corrosion. Polymer materials are being explored for bone implants due to their light‐weight, biocompatibility, biodegradability, and absence of stress sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 166 publications
0
25
0
Order By: Relevance
“…Moreover, the bioinert behavior of PEEK has prompted researchers to tailor its biocompatibility using surface modifications and render it for biomedical applications. [108] Han et al reported coating of pure titanium layer onto PEEK using electron beam deposition. [109] This lowtemperature method deposited crystalized titanium and ensured that the properties of PEEK were not altered.…”
Section: Peek Surface Modificationsmentioning
confidence: 99%
“…Moreover, the bioinert behavior of PEEK has prompted researchers to tailor its biocompatibility using surface modifications and render it for biomedical applications. [108] Han et al reported coating of pure titanium layer onto PEEK using electron beam deposition. [109] This lowtemperature method deposited crystalized titanium and ensured that the properties of PEEK were not altered.…”
Section: Peek Surface Modificationsmentioning
confidence: 99%
“…These coatings act as a physical barrier to separate metal surfaces from corrosive environments. [5][6][7][8] Due to its high mechanical strength, thermal stability, chemical resistance, hydrophobicity, and excellent electroactive properties, poly(vinylidene fluoride) (PVDF) is being used in a wide range of engineering applications. [9][10][11][12][13] PVDF has also been extensively used in the films and coatings industry.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM) technology provides the ideal tailor-made solution for different orthopedic applications. [1] This technology offers various merits and functionalities such as precision, [2] ease of the process, [3] less material wastage, [4] personalization, [5] degree of freedom, [6] accuracy, [7] biocompatibility, [8] and customization [9] for the…”
Section: Introductionmentioning
confidence: 99%